Recent trends in platelet membrane-cloaked nanoparticles for application of inflammatory diseases. (31st December 2022) - Fang, Zhengyu; Fang, Jie; Gao, Chunxiao; Gao, Rui; Lin, Peihong; Yu, Wenying
Abstract: Platelets are multifunctional effectors of inflammatory responses and inseparable from the occurrence and development of various inflammatory diseases. The platelet membrane (PM) is integrated onto the surface of a nano-drug delivery system to form the PM-cloaked nanoparticles (PM@NPs), which can increase the biocompatibility of the nano-drug delivery system and mitigate adverse drug reactions. Owing to the strong affinity of immune regulation and adhesion-related antigens on the surface of PM to the focal sites of inflammatory diseases, which endows PM@NPs with the potential to actively target lesions and improve the therapeutic efficacy of drugs for inflammatory diseases. Based on latest developments in PM biomimetic technique and nanomedicine for the treatment of inflammatory diseases, this paper mainly elaborates three aspects: advantages of PM@NPs, experimental foundation of PM biomimetic nanotechnology, and applications of PM@NPs to the treatment of inflammatory diseases. The aim is to provide reference for the development and application of PM@NPs and novel insights into the treatment of inflammatory diseases.